Goths and Greeks: the rise of Anglo-Saxon England and Germanic English in early modern Britain - Massimiliano Morini (Filologia Germanica)
If the Elizabethan age was the period during which the European Renaissance came to England by means of translation – as famously put by F.O. Matthiessen in 1931 – it was also, somewhat paradoxically, the time of birth of Old English scholarship and historical research into the AngloSaxon Middle Ages. After Elizabeth I’s accession, a group of antiquarians, religious reformers and linguists began to propose a vision of “England” (and not “Britain”) relying on the histories and myths of the Germanic tribes that had invaded the island a millennium before, rather than on some legendary connection with the matter of Troy. Partly – and again, paradoxically – this new interest arose as a consequence of the new philological and historical methods developed by classical humanists; partly, though, it was promoted by important political figures who saw its possibilities in terms of political and religious propaganda. In the latter half of the century, when Britain was trying to consolidate its position as a relatively isolated Protestant power, the ideological advantages of presenting “England” as radically different from the Graeco-Roman south must have seemed evident to such figures as Archbishop Matthew Parker and Secretary of State William Cecil. As a reflection of this changed political climate, from the 1560s onwards, several academic and literary figures began to exalt the purity of Germanic English and the virtues of England’s “Gothic” and “Saxon” past – thus entering into an explicit or implicit dispute with those who thought that the nation had to build its glory upon classical foundations. By the beginning of the seventeenth century, the idea of England as a Germanic nation forged in the Anglo-Saxon Middle Ages was fully formed – and though that lies outside the scope of the article, its influence on the concept of “Englishness” lingers to this day.